Granting Agency Criteria for Awarding Graduate Research Scholarships - O’Brecht, Michael; Pihl, Robert O. (Canadian Journal of Higher Education, 1991)
Eleven Canadian research granting agencies were surveyed concerning the weights that they apply to various criteria when reviewing applications for graduate student awards. Nine agencies responded, seven providing useful data. The undergraduate academic grades of applicants for research training awards were found to carry high weight in selection decisions, especially in competitions that were either large or were open to students at the master's level. However, the literature on early career indicators suggests that the undergraduate academic achievement of graduate students is not an effective predictor of their future research productivity. Strategies through which agencies might improve the use of more predictive criteria, such as applicant characteristics and quality of the graduate training environment, are discussed.